EFEKTIFITAS PENGGUNAAN KOMPRES HANGAT TERHADAP NYERI PERSALINAN DI BPM DAWARBLANDONGMOJOKERTO - Rahmawati, Ima; Iswati (JURNAL KEPERAWATAN SEHAT, 2016)
Labor is a series of events that ended with a pretty baby spending months or almost enough months followed by spending on the placenta and fetal membranes from the body of the mother. Labor is divided into four stages, namely kala I labor (kala), kala (kala spending fetus), kala (kala spending placenta) and kala (kala supervision)IV. The purpose of this research is to know the effectiveness of the use of warm compresses against the labor pain at the maternity mother kala 1 in bpm umrotul ustadah UR amd.keb dawar blandong mojokerto. The design of this research is to approach pre-Ekperimental. Variables in research that is warm compresses as the independent variable and the dependent variable as a labor pain. Research population that is as much as 8 respondents and samples taken with the accidental sampling techniques. Data taken using a warm compress observation sheet instruments and observation sheet labor pain using the measuring instrument Bourbanais Scale value. Based on statistical tests are performed using test wilxocon ? = 0.023 results of this research show that there are influences of the scale of pain after being given a warm compress where this sign as seen from changes of scale of pain before given a warm compress, while after being given a warm compress for 10-15 minutes, and the respondents are already reduced to not seem in pain again. It can be noted that there is the effectiveness of the use of warm compresses against the labor pain at the maternitymother kala I.Keywords: Warm Compress, Pain